1999
DOI: 10.1680/geot.1999.49.5.621
|View full text |Cite
|
Sign up to set email alerts
|

Wave-induced liquefaction of beds of sand in a centrifuge

Abstract: The behaviour of beds of fine-grained sand under fluid wave trains was investigated using centrifuge modelling. Three sets of centrifuge wave tank tests with viscous scaling were performed, such that time-scaling laws for wave propagation as well as consolidation were matched. The test programme consisted of either progressive- or standing-wave tests on loosely packed, fresh deposits of soil, as well as repeated travelling-wave tests with intervening periods of consolidation. The results from the progressive- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
116
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(124 citation statements)
references
References 0 publications
6
116
0
2
Order By: Relevance
“…They concluded that pore water pressure fluctuations in the seabed due to short period waves are significant and are affected by the soil permeability and deformability, and wave-induced liquefaction is related to the upward seepage flow induced in the sea bed during the passage of wave troughs [16]. To understand the soil behavior in a controlled setting, wave tank experiments [14,19,33,39,41,42,47], compressive tests [12,51], and centrifugal wave tank studies [29,30,32] have also been conducted. Wave tank experiments have the advantage that they can provide the spatial and temporal distribution of the wave-induced pressures at the structure and at the bed surface.…”
Section: Previous Work On Wave-seabed Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that pore water pressure fluctuations in the seabed due to short period waves are significant and are affected by the soil permeability and deformability, and wave-induced liquefaction is related to the upward seepage flow induced in the sea bed during the passage of wave troughs [16]. To understand the soil behavior in a controlled setting, wave tank experiments [14,19,33,39,41,42,47], compressive tests [12,51], and centrifugal wave tank studies [29,30,32] have also been conducted. Wave tank experiments have the advantage that they can provide the spatial and temporal distribution of the wave-induced pressures at the structure and at the bed surface.…”
Section: Previous Work On Wave-seabed Interactionsmentioning
confidence: 99%
“…To overcome the 1g limitation and to provide spatial distribution of the wave loads, Sekiguchi and Phillips [32] and Phillips and Sekiguchi [29] developed a novel setup to conduct wave experiments in a centrifuge. Viscous scaling was used to satisfy the time-scaling laws for fluid wave propagation and the consolidation of the soil [30]. However, the study was limited to short period progressive or standing waves with an equivalent field period of 4.5 s over a flat bottom.…”
Section: Previous Work On Wave-seabed Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakai et al (1992) reported sinking concrete blocks at a beach in Japan, and proved that liquefaction is a theoretically consistent explanation for the observed beach sediment instability. Such theories were supported by laboratory studies by, e.g., Clukey et al (1985); Sassa and Sekiguchi (1999).…”
Section: Introductionmentioning
confidence: 74%
“…1), as well as vibration of structures or seismic activity. Since the 1990s researchers have successfully demonstrated and investigated this effect in wave tanks and numerical simulations (Sakai et al, 1992;De Wit and Kranenburg, 1997;Sassa and Sekiguchi, 1999;Osinov, 2000;Sassa and Sekiguchi, 2001;Jeng et al, 2004;Mutlu Sumer et al, 2006). Momentary liquefaction has gained in importance regarding observations of unexpectedly strong erosion, for example at beaches during storm events and in connection with scour.…”
Section: Introductionmentioning
confidence: 99%